Class III phosphatidylinositol 3–kinase and its catalytic product PtdIns3P in regulation of endocytic membrane traffic. (6th February 2013) - Raiborg, Camilla; Schink, Kay O.; Stenmark, Harald
<x xml:space="preserve">Abstract</x> Endocytosis and subsequent membrane traffic through endosomes are cellular processes that are integral to eukaryotic evolution, and numerous human diseases are associated with their dysfunction. Consequently, it is important to untangle the molecular machineries that regulate membrane dynamics and protein flow in the endocytic pathway. Central in this context is class III phosphatidylinositol 3–kinase, an evolutionarily conserved enzyme complex that phosphorylates phosphatidylinositol into phosphatidylinositol 3–phosphate. Phosphatidylinositol 3–phosphate recruits specific effector proteins, most of which contain FYVE or PX domains, to promote endocytosis, endosome fusion, endosome motility and endosome maturation, as well as cargo sorting to lysosomes, the biosynthetic pathway or the plasma membrane. Here we review the functions of key phosphatidylinositol 3–phosphate effectors in regulation of endocytic membrane dynamics and protein sorting.